Synthetic Access to a Pure Polyradical Architecture: Nucleophilic Insertion of Nitronyl Nitroxide on a Cyclotriphosphazene Scaffold. Issue 12 (14th December 2017) - Fidan, Ismail; Önal, Emel; Yerli, Yusuf; Luneau, Dominique; Ahsen, Vefa; Hirel, Catherine
Abstract: An optimized nucleophilic synthetic approach featuring mild conditions and microwave energy was utilized to circumvent the classical Ullman procedure and access a polynitronyl nitroxide radical easily and in pure form. The simultaneous controlled introduction of preformed nitronyl nitroxide radicals on a cyclotriphosphazene core leads to a novel polyphosphazene monomer which is suitable for both n‐ and a p‐type redox‐active material in organic rechargeable batteries as demonstrated by electrochemistry. Additionally, absorption spectra and square‐wave voltammetry were utilized to quantify the number of nitronyl nitroxide radical units on the cyclotriphosphazene scaffold. Abstract : Radical purity : In the synthesis of nitronyl nitroxide polyradicals, the classical Ullman strategy results in a mixture of nitronyl and imino nitroxide moieties on the same framework. An alternative nucleophilic synthetic approach based on mild conditions and microwave energy was optimized to introduce preformed nitronyl nitroxide units simultaneously to provide a pure polynitronyl nitroxide compound (see scheme). UV/Vis spectroscopy and square‐wave voltammetry were used to quantify the number of radical moieties on the cyclotriphosphazene scaffold.